Toxicity of Magnesium Sulphate to Nile Tilapia (Oreochromis niloticus) - Chandra, Ishwar; Ittoop, Gijo; Pillai, Devika; A, Rehna; Chandrasekhar, Leena; Nair, Suresh N (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Magnesium sulphate commonly known as Epsom salt is used in aquaculture in order to treat intestinal problems related to digestion or parasites. In the present study an effort was made to understand the toxicity of magnesium sulphate in sub adults of Oreochromis niloticus (82± 4.5g). Acute toxicity test by bath treatment was done by exposing the fish to magnesium sulphate at concentrations of 0 gL-1, 10 gL-1 30 gL-1and 60 gL-1as per OECD 203 guidelines for 96 hours. Acute oral toxicity was done as per Limit test of OECD 425 guidelines. After the completion of experimental period, blood was collected and hematological parameters like total leucocytes, erythrocytes, thrombocytes, haemoglobin, haematocrit, mean corpuscular volume and mean corpuscular haemoglobin were estimated. Serum parameters like Aspartate transaminase (AST), Alanine transaminase (ALT), blood urea nitrogen (BUN), and creatinine (CRE) were determined. The antioxidant enzymes like superoxide dismutase, catalase and reduced glutathione in the gill and liver tissue were also estimated. Fish were euthanized and the histopathology of intestine, liver, muscle, gills and heart was done. The toxicity tests by oral and bath administration did not cause mortality in fish with the respective doses. In the bath treatment test, the serum parameters like AST, ALT, CRE and BUN showed significant difference at concentrations above 30gL-1. Histological observations also revealed pathologies in all the tissues at 30gL-1. In oral toxicity tests, there was no significant difference in any of the parameters tested between control and treatment groups. The results revealed that Epsom salt is non-toxic to O. niloticus, and can be used as a chemotherapeutant without any toxic effect when administered orally. For bath treatments, the fish can tolerate upto 10gL-1 without any toxic effect.